PEMBUATAN GAME “BLAST OFF” MENGGUNAKAN UNITY - Dannny Kristianto; Jeanny Pragantha; Darius Andana Haris (Jurnal Ilmu Komputer dan Sistem Informasi, 2016)
“Blast Off” is a physics puzzle 2D game which is developed under game development software Unity. The player controls a member of demolition squad who test an experimental type of bomb. Player uses a variety of bombs with different special effects to destroy buildings. Testing is done with questionnaires filled out by 30 respondents. The results from the testing is an improvement in design and visual quality of the game.